Coincubation as miR-Loading Strategy to Improve the Anti-Tumor Effect of Stem Cell-Derived EVs - Alessia Brossa; Marta Tapparo; Valentina Fonsato; Elli Papadimitriou; Michela Delena; Giovanni Camussi; Benedetta Bussolati (MDPI AG, 2021)
Extracellular vesicles are considered a novel therapeutic tool, due to their ability to transfer their cargoes to target cells. Different strategies to directly load extracellular vesicles with RNA species have been proposed. Electroporation has been used for the loading of non-active vesicles; however, the engineering of vesicles already carrying a therapeutically active cargo is still under investigation. Here, we set up a coincubation method to increase the anti-tumor effect of extracellular vesicles isolated from human liver stem cells (HLSC-EVs). Using the coincubation protocol, vesicles were loaded with the anti-tumor miRNA-145, and their effect was evaluated on renal cancer stem cell invasion. Loaded HLSC-EVs maintained their integrity and miR transfer ability. Loaded miR-145, but not miR-145 alone, was protected by RNAse digestion, possibly due to its binding to RNA-binding proteins on HLSC-EV surface, such as Annexin A2. Moreover, miR-145 coincubated HLSC-EVs were more effective in inhibiting the invasive properties of cancer stem cells, in comparison to naïve vesicles. The protocol reported here exploits a well described property of extracellular vesicles to bind nucleic acids on their surface and protect them from degradation, in order to obtain an effective miRNA loading, thus increasing the activity of therapeutically active naïve extracellular vesicles.